2021
DOI: 10.3390/medicina57101134
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review to Assess the Impact of Hyperbaric Oxygen Therapy on Glycaemia in People with Diabetes Mellitus

Abstract: Background and Objectives: Hyperbaric oxygen is a recognised treatment for a range of medical conditions, including treatment of diabetic foot disease. A number of studies have reported an impact of hyperbaric oxygen treatment on glycaemic control in patients undergoing treatment for diabetic foot disease. There has been no systematic review considering the impact of hyperbaric oxygen on glycaemia in people with diabetes. Materials and Methods: A prospectively PROSPERO-registered (PROSPERO registration: CRD420… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In addition to the possible positive effects on glucose metabolism during normal aging, HBOT has shown clinical efficacy in lowering blood glucose and improving insulin sensitivity in type 2 diabetes mellitus [ [164] , [165] , [166] , [167] ], the most common age-related metabolic disorder. Notably, the majority of participants in these studies received HBOT for treatment of diverse conditions including non-healing ulcers and diabetic foot ulcers, leading to an older age range [ 165 ]. It suggests that these conclusions may be more applicable to the elderly diabetic population.…”
Section: Therapeutic Implications Of Hbot In Aging Interventionmentioning
confidence: 99%
“…In addition to the possible positive effects on glucose metabolism during normal aging, HBOT has shown clinical efficacy in lowering blood glucose and improving insulin sensitivity in type 2 diabetes mellitus [ [164] , [165] , [166] , [167] ], the most common age-related metabolic disorder. Notably, the majority of participants in these studies received HBOT for treatment of diverse conditions including non-healing ulcers and diabetic foot ulcers, leading to an older age range [ 165 ]. It suggests that these conclusions may be more applicable to the elderly diabetic population.…”
Section: Therapeutic Implications Of Hbot In Aging Interventionmentioning
confidence: 99%
“…There is evidence suggesting a reduction in glycemia following HBOT in patients with diabetes mellitus, but the sample size is small and potentially underpowered. 29 There are a few limitations to the study. Only subjects with symptoms onset of ≤6 hours were included, and thus many patients were unable to benefit from HBOT, although the Undersea and Hyperbaric Medical Society recommends HBOT within 24 hours of symptoms onset.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the use of HBO in type 2 DM reduced hypoxia in tissues, reduced blood glucose, increased insulin secretion, increased target cell insulin sensitivity, and normalized an imbalance of the antioxidant system [15,16]. Until recently, there have been limited reports on the use of HBO in DR.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of oxidative processes causes the formation of a branched system protecting tissues from damage by aggressive oxygen radicals [superoxide anion radical (O2-), hydroxyl radical (HO-) and hydrogen peroxide Н2О2]. SOD family enzymes catalyze the dismutation of superoxide radicals into oxygen and hydrogen peroxide peroxide, and CAT catalyzes the conversion of hydrogen peroxide to water and molecular oxygen [11][12][13][14][15][16]. GSR provides restoration of the reduced form of glutathione [17], which significantly decreases the risk of oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation